Genotypic and environmental effects on starch properties of Argentinean wheat flours. (25th April 2016) - Vignola, María B.; Baroni, Verónica; Pérez, Gabriela T.
Abstract : The aim of this study was to determine the influence of different environments and genotypes on starch characteristics and properties of Argentinean wheat flours. Amylose content, starch granule size distribution, thermal characteristics, and pasting properties of flours were determinate on 24 wheat genotypes from six environments. There were significant differences for all parameters analyzed among genotypes and environments ( p  < 0.05). The environment was the main factor responsible for the increase of variability observed in amylose content. According to variance ratios, environmental conditions have a greater influence on the characteristics of A granules, while genotype influenced mostly B granules diameter and volume percentage. Balcarce‐2010 and Reconquista‐2010, environments which showed drought during grain filling, were the environments that presented the highest volume percent of B granules and the lowest percent of A granule. Genotype was the greatest source of variation, according to variance relationship, for DSC parameters. ΔH values were the highest on MarcosJuarez‐2009 and Reconquista‐2010 where high temperatures during grain filling period were recorded. Besides, these two environments also presented high pasting temperature values. Environment had a noticeable greater impact on starch properties of wheat than genotype for all pasting properties parameters except for pasting temperature. Both genetic and environmental factors control physicochemical characteristics of starch and the size distribution of starch granules in wheat grains at different degrees.